2020
DOI: 10.1021/acssuschemeng.0c06191
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Process Understanding of the Biomimetic Construction of Porphyrin-Based Light-Capturing Antennas from Self-Assembled Fmoc-Blocked Peptide Templates

Abstract: Natural photosynthesis provides a perfect example of solar energy utilization that converts CO2 to carbohydrates at high efficiency. Herein, an innovative approach was developed to construct light-harvesting antennas via the precise control of porphyrin aggregation and platinum organization on the surface of the self-assembled structures of Fmoc-blocked peptides (Fmoc-ChaChaGK-NH2 and Fmoc-FFGK-NH2). The photophysical properties and the photocatalytic activity of the antenna are dependent on the aggregating st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…In this work, we used second harmonic generation (SHG) and sum-frequency generation (SFG) technologies to study the supramolecular self-assembly dynamics and chirality transfer of TPPS molecules at l -/ d -G12 amphiphilic monolayers (Figure ). TPPS, a porphyrin derivative often used as a typical photosensitive agent, constructs light-collecting antennas and chiral supramolecular functional materials by precisely controlling the aggregation of porphyrins. Although TPPS is an achiral molecule, it can self-assemble with intrinsic chiral molecules (such as amino acid molecules) through a variety of synergies of molecular interaction to form self-assembly with supramolecular chirality . We found that TPPS molecules in a saddle-shaped conformation adsorbed onto an amphiphilic cationic monolayer by electrostatic forces and then formed chiral supramolecular assemblies (Figure , right).…”
mentioning
confidence: 93%
“…In this work, we used second harmonic generation (SHG) and sum-frequency generation (SFG) technologies to study the supramolecular self-assembly dynamics and chirality transfer of TPPS molecules at l -/ d -G12 amphiphilic monolayers (Figure ). TPPS, a porphyrin derivative often used as a typical photosensitive agent, constructs light-collecting antennas and chiral supramolecular functional materials by precisely controlling the aggregation of porphyrins. Although TPPS is an achiral molecule, it can self-assemble with intrinsic chiral molecules (such as amino acid molecules) through a variety of synergies of molecular interaction to form self-assembly with supramolecular chirality . We found that TPPS molecules in a saddle-shaped conformation adsorbed onto an amphiphilic cationic monolayer by electrostatic forces and then formed chiral supramolecular assemblies (Figure , right).…”
mentioning
confidence: 93%
“…[54] All of the successful peptide scaffolds discussed, with the exception of di-lysine, also contain hydrophobic amino acids. [26,27,36,[53][54][55][56][57][58] Taken together, it appears there is a balance of cationic charge, hydrophobicity, and aromatic groups that combine to provide a suitable platform for J-aggregate assembly and formation of larger meso-scale aggregates. Importantly, while not evident in our current system, TPPS 4 peptide complexes have been shown to form H-aggregates under certain conditions and would also potentially impact future designs.…”
Section: Peptide-tpps 4 Aggregatesmentioning
confidence: 99%
“…[26,30,31,35,37,49,51,52] Short cationic peptides have been demonstrated to act as scaffolds to facilitate TPPS 4 assembly. [26,[27][28][29]36,53,[53][54][55][56][57][58] Supramolecular nanowires made from J-aggregates of TPPS 4 have potential as building blocks of self-assembling photomaterials if more robust assembly could be achieved under a wider range of conditions.…”
mentioning
confidence: 99%
“…Xiu et al compared the co-assembly of tetrakis(4-sulfonatophenyl)porphyrin and Pt particles with similar peptides ( 51a – d ) to understand how the peptide molecular structure influences the light harvesting system [ 110 , 111 ]. The Fmoc group and the Cha residue ( 51a ) promoted the assembling and the formation of J-aggregates, enhancing the photo-to-electric conversion efficiency and photocatalytic ability (NAD+/NADH conversion) of these architectures.…”
Section: Peptides Containing Non-amino Acid Componentsmentioning
confidence: 99%
“…In tetrahydrofuran/water, vesicles with variable size and distribution depending on the molar ratio of the two components are formed, while the addition of trifluoroethanol promotes the transition from supramolecular vesicles to the fiber morphology. -d) to understand how the peptide molecular structure influences the light harvesting system [110,111]. The Fmoc group and the Cha residue (51a) promoted the assembling and the formation of J-aggregates, enhancing the phototo-electric conversion efficiency and photocatalytic ability (NAD+/NADH conversion) of these architectures.…”
Section: Other Biomoleculesmentioning
confidence: 99%